From the chaos of transition economy to 'normalized' managerial practices: The role of group interaction in creating meaning in managerial work - Svetlana Serdukov (Journal for East European Management Studies, 2012)
The purpose in this paper is to explore the interplay between managerial sensemaking, representations and identity in the context of a transition economy. Using the approach of theory of social representations (Moscovici, 1961), a thirteen year long observation of a group of twelve owners/managers was adopted. The research concluded that managerial practices emerged in social interaction. These practices existed in relations of co-production and were embedded in the social construct. During the transition period, the content of managerial actions, narratives and identity changed in the same way under the influence of shared culture, ideologies and day-to-day social practices. This is one of the rare longitudinal studies of transition economies where the process of emergence of a small social group was observed and the pattern of evolution identified. – – Zweck dieser Arbeit ist die Untersuchung des Zusammenspiels zwischen Sensemaking, Repräsentationen und Identität im Kontext einer Transitions- Wirtschaft. Auf der Grundlage der Theorie der sozialen Repräsentationen (Moscovici, 1961) wurde eine Gruppe von 12 Eigentümern/Managern während 13 Jahren beobachtet. Die Untersuchungen ergaben, dass Managementpraktiken in der sozialen Interaktion entstehen. Diese Praktiken bestanden aus den Beziehungen der Co-Produktion und wurden in ein soziales Konstrukt eingebettet. Während der Übergangszeit wandelte sich der Inhalt des Managerhandelns, der Narrationen und der Identität in gleicher Weise unter dem Einfluss der gemeinsamen Kultur, Ideologien und von alltäglichen sozialen Praktiken. Dies ist eine der seltenen Längsschnittstudien über Transitions- Wirtschaften, in denen der Prozess der Entstehung einer kleinen sozialen Gruppe beobachtet und ihr Evolutionsmuster identifiziert wurde.
Keywords: 650; transition; ideology; identity; longitudinal; Kazakhstan